ChemInform Abstract: Room Temperature Magnetic Rare‐Earth Iron Garnet Thin Films with Ordered Mesoporous Structure. Issue 35 (8th August 2013) - Suchomski, Christian; Reitz, Christian; Sousa, Celia T.; Araujo, Joao P.; Brezesinski, Torsten
Abstract Highly crystalline thin films of lanthanoid Fe garnet (Ln3Fe5O12, Ln: Y, Gd, Tb, Dy) with cubic networks of interconnected pores (average 17 nm in diameter) are prepared through facile polymer (poly‐ω‐hydroxypoly(ethylene‐co‐butylene)‐co‐poly(ethylene oxide)) templating of hydrated nitrate salts in methoxyethanol and EtOH.